DYNAMIC COUPLING MODELING FORMED BY TURNING IN CUTTING DYNAMICS PROBLEMS (VELOCITY COUPLING) - Vilor L. Zakovorotniy (Advanced Engineering Research, 2011)
Mathematical simulation and parameter identification of dynamic coupling between the tool and workpiece, formed through cutting, are considered. Data on the dynamic coupling characteristics under small variations of the coordinates in the neighborhood of equilibrium point are resulted. The coupling presented by the matrix of velocity coefficients is investigated.